Teaching strategies for developing productive-divergent thinking among fast learners - Aquintey, Mary L.; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1976)
The study is based on Williams' model for developing productive-divergent thinking. A lesson plan budget incorporated three class subjects, Social Studies, Science and Language (Dimension 1) using the classroom eaching strategies (Dimension 2) to bring about the seven productive-divergent thinking processes (Dimension 3). Thus, Williams' formula became the framework which the twenty six children enrolled in the Accelerated class were exposed to for a period of seven days.
Thesis (Master of Arts in Teaching Special education - Giftedness)--University of the Philippines, Diliman
Keywords: Creative thinking in children -- Study and teaching -- Philippines -- Pasay City; Gifted children -- Education (Elementary) -- Activity programs -- Philippines -- Pasay City